2015
DOI: 10.1210/jc.2014-3678
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High-Fructose Weight-Maintaining Diet on Lipogenesis and Liver Fat

Abstract: Short-term high-fructose intake was associated with increased DNL and liver fat in healthy men fed weight-maintaining diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
180
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(195 citation statements)
references
References 39 publications
14
180
1
Order By: Relevance
“…We have recently shown that in healthy adults fed isocaloric diets, DNL and liver fat were higher during high-fructose feeding, when compared with low-fructose feeding. 18 Those results, taken together with those of the present study, support the hypothesis that DNL is an important mechanism in the modulation of liver fat. 8, 3542 Moreover, the increases in VAT with high-fructose feeding 2 and the decrease in VAT observed with fructose restriction observed in the present study suggest primary links between fructose consumption, DNL, and ectopic fat.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have recently shown that in healthy adults fed isocaloric diets, DNL and liver fat were higher during high-fructose feeding, when compared with low-fructose feeding. 18 Those results, taken together with those of the present study, support the hypothesis that DNL is an important mechanism in the modulation of liver fat. 8, 3542 Moreover, the increases in VAT with high-fructose feeding 2 and the decrease in VAT observed with fructose restriction observed in the present study suggest primary links between fructose consumption, DNL, and ectopic fat.…”
Section: Discussionsupporting
confidence: 90%
“…We recently demonstrated that in weight-stable healthy men, high fructose intake for a 9-day period was associated with higher DNL and liver fat, compared with a diet with identical energy and macronutrient intake, but in which complex carbohydrate (starch) was substituted for sugar. 18 Thus we provided evidence linking fructose-driven DNL with liver fat and demonstrated that short-term reduction in fructose intake was consistently associated with lower levels of liver fat and rates of DNL, even in the absence of weight loss.…”
Section: Introductionmentioning
confidence: 66%
“…85 Markedly reducing intake of added sugars, especially sucrose and HFCS, can lead to NAFLD regression and, presumably, reduction of associated CHD risk. 87, 88 …”
Section: Sugar and Chd Risk Factorsmentioning
confidence: 99%
“…Schwarz et al demonstrated that de novo lipogenesis was ~60% higher in healthy men fed an isocaloric, high-fructose diet (25% calories) for nine days relative to when the subjects ate a complex carbohydrate diet [9]. Le et al compared normoglycemic, lean, insulin sensitive individuals with normoglycemic and lean, but insulin resistant offspring of patients with T2DM before and after 7 days of a hypercaloric diet in which an additional 35% of their calories were derived from fructose [10].…”
Section: High Fructose Consumption Rapidly Impacts Metabolismmentioning
confidence: 99%